POWAGA KANONU I PROPOZYCJA Z DYSTANSU (TERESA FERENC)* - Łukaszuk, Małgorzata (Colloquia Litteraria, 2016)
The article, in the first part, brings forward a proposal for the understanding of the canon as an axiological contract in which a given work reveals its true importance and validity aside from methodological and world-view conjunctures. In the second part, the author situates poetic works of Teresa Ferenc within the sphere of importance. The article uses concepts such as appreciation, gravity, merger, affirmation, good, importance, distinction, reduction taken from the hermeneutics of Ricoeur and Gadamer.